“Living Originalism”: Jack M. Balkin - Verdugo, Sergio (Derecho Público Iberoamericano, 2020)
Jack M. Balkin. "Living Originalism" (Originalismo vivo), Cambridge, Massachusetts, London, The Belknap Press of Harvard University Press, 2011 (ISBN 978-0-674-06178-1).